Pond/ditch benthic invertebrate data on d15N/d13C (northeast-Germany, 2020) - Fee Nanett Trau; Stefan Lorenz (PANGAEA, 2025)
Benthic invertebrate samples were taken directly in the field via hand-netting in four ditches and three ponds (defined as water bodies with a maximum extent of one hectare) in October and November 2020. Sampling was carried out in Brandenburg in Germany in the region Havellaendisches Luch. The landscape is characterized by an intensively maintained ditch system that was created for industrial agricultural production during 1980s. Additionally, the landscape is characterized by a large number of small standing water bodies (kettle holes, ponds), which were formed during the last glacial period. A detailed description of the area can be found in Trau & Lorenz, 2024. Invertebrate samples were analysed for the stable isotopes of carbon and nitrogen. The data set includes data from 35 families. The whole animal was used for the analysis of stable isotopes of carbon and nitrogen. Analyses were performed on a Thermo Delta V isotope ratio mass spectrometer (IRMS) interfaced to a NC2500 elemental analyser by the Cornell University Stable Isotope Laboratory (https://cobsil.cornell.edu/). The dataset was used to evaluate isotopic niches of functional feeding groups (collector/gatherer, collector/filterer, grazer/scraper, shredder, predator and omnivore) in the two water body types (pond and ditch), in order to evaluate effects of agriculture (nutrient concentrations and pesticide residues) on the isotopic niches (Trau et al. 2025, under review).